Attention to Student Writing in Postgraduate Health Science Education: Whose Task is It – or Rather, How? - Leibowitz, Brenda (Journal of Academic Writing, 2013)
This article reports on an action research study designed to stimulate the metacognitive awareness of the writing of assignments in English of a group of students from diverse language and educational backgrounds, studying health science education at masters level. In the study, students were required to give and receive feedback on a marked written assignment to a peer, and receive feedback from a consultant working at the Writing Lab. They were then required to submit a reflective report, which constitutes the key data source for this study. An analysis of the reflective reports revealed that the students claimed that they learnt about their writing habits, about good academic writing, and about the experience of giving and receiving feedback. The study suggests that although an intervention making extensive use of a variety of sources of feedback appears to be able to stimulate students’ metacognitive functioning in relation to their writing of assignments, a number of issues require concerted attention. These issues include: power relations and emotion, perceptions of legitimate authority, and the central role of the lecturer as disciplinary expert and guide. The article concludes with a recommendation for enhanced attention to intersubjective relations of power, language and identity in relation to feedback on writing, especially when peer feedback is involved.